Acute phosphate nephropathy after sodium phosphate preparations. (17th July 2008) - Connor, Andrew; Sykes, Lucy; Roberts, Ian S D; Weston, Charles E
Abstract : Predisposed individuals may develop chronic kidney disease after administration of sodium phosphate purgative before colonoscopy